1991
DOI: 10.1080/01688639108401083
|View full text |Cite
|
Sign up to set email alerts
|

Memory and attention in patients with senile dementia of the alzheimer type and in normal elderly subjects

Abstract: Previous studies have shown that cholinergic blockade in normal subjects induces impairment of vigilance as well as memory deficits. In the present investigation we have examined the validity of this pharmacological model of dementia by administering a battery of cognitive tasks to patients with mild and moderate senile dementia of the Alzheimer type and to age-matched controls. In contrast to volunteers receiving scopolamine all the mildly demented patients, and half of those moderately affected, performed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
1
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 39 publications
2
21
1
1
Order By: Relevance
“…These findings give evidence for deficient processing resources of the Central Executive in early stages of Alzheimer's disease. In contrast to other studies (Lines et al, 1991), we did not find a preserved spatial span. Compared to healthy controls, patients performed significantly worse on the standard Corsi task.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings give evidence for deficient processing resources of the Central Executive in early stages of Alzheimer's disease. In contrast to other studies (Lines et al, 1991), we did not find a preserved spatial span. Compared to healthy controls, patients performed significantly worse on the standard Corsi task.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have found that forward digit span does not differ between AD patients and cognitively intact elderly controls (Botwinick, Storandt, & Berg, 1986;Carlesimo, Fadda, Lorusso, & Caltagirone, 1994;Lines et al, 1991;Martin, Browers, Cox, & Fedio, 1985;Orsini, Trojano, Chiacchio, & Grossi, 1988) and shows minimal decline in early AD (Botwinick et al, 1986). These ®ndings indicate that the phonological loop is generally intact in mild AD (Perry & Hodges, 1999).…”
mentioning
confidence: 87%
“…Some investigators have examined subjects at the very early stages of AD, referred to as 'minimal AD' and at the preclinical or 'mild cognitive impairment' (MCI) stage. There is evidence that digit spans are preserved in MCI and minimal AD but become significantly impaired across mild and moderate groups (Corkin, 1982;Orsini et al, 1988;Lines et al, 1991;Greene et al, 1995;Hodges and Patterson, 1995;Traykov et al, 2007). This may reflect initially normal functioning within the phonological loop and CES which becomes impaired as the disease progresses.…”
Section: Impairment Of Memory Span Tasks In Admentioning
confidence: 99%
“…This involves encoding of visual stimuli, short term storage of spatial location and sequence order and maintenance of information over time (Fischer, 2001). As reviewed in Table 2, impairment on this task has been found in both mild and moderate AD groups compared to both young and elderly controls but not in MCI (Corkin, 1982;Orsini (Morris, 1984) 17 AD MOD Impaired 17 EC ('Moderate severe anterograde amnesia and moderately disorientated') (Martin et al, 1985) 14 AD MILD Intact 11 EC (WAIS, WMS) (Kopelman, 1985) 16 AD MILD-MOD Impaired 16 Korsakoff (NART, IQ, Wechsler logical memory) 16 EC (Morris, 1987a) 21 AD MILD Impaired 21 EC (WAIS and clinical evidence) (Becker, 1988) 71 AD MILD (MMSE 22.5 (5.2)) Impaired 89 EC (Spinnler et al, 1988) 29 AD MILD-MOD Impaired 42 YC (Psychometric assessment) 58 EC (Orsini et al, 1988) 51 AD MILD (n ¼ 24) Intact 30 EC MOD (n ¼ 27) Impaired (History, orientation, visual retention test, clinical judgement) (Lines et al, 1991) 16 AD MILD (n ¼ 8, MMSE 22 (20-26)) Intact 8 EC MOD (n ¼ 8, MMSE 11-19) Impaired (Hulme et al, 1993) 14 AD MILD Impaired 14 EC (relatively early stage of dementia, Clifton assessment procedure) (Carlesimo et al, 1994) 18 AD MILD Intact 18 MID (Global performance index) 26 EC (Hodges and Patterson, 1995) 52 AD MIN (n ¼ 17, MMSE 25.6 (1.8)) Intact 24 EC MILD (n ¼ 17, MMSE 20.9 (1.7)) Impaired MOD (n ¼ 18, MMSE 10 (4.6)) Impaired (Greene et al, 1995) et al., 1988;Spinnler et al, 1988;Sahgal et al, 1992;Grossi et al, 1993;Carlesimo et al, 1994;Trojano et al, 1994;Cherry et al, 1996). As the Corsi block tapping task requires both visuospatial storage and executive processing (temporal sequencing), the impairment seen in early AD, on both forward and backward spatial spans, has been interpreted as reflecting deficits in both the VSS and central executive (Carlesimo et al, 1994).…”
Section: Impairment Of Memory Span Tasks In Admentioning
confidence: 99%